PENGARUH GAYA HIDUP, CITRA MEREK DAN FREE GIFT TERHADAP KEPUTUSAN PEMBELIAN DI BOOST JUICE BARS SUMMARECON MALL BEKASI - Rosdiana Naila; Chatarina Yunita Tarigan (LPPM Universitas Asa Indonesia, 2025)
The purpose of this research is to analyze the effect of lifestyle, brand image, and free gifts on purchase decisions at Boost Juice Bars Summarecon Mall Bekasi. Using a quantitative approach and accidental sampling of 100 respondents, data were analyzed through multiple linear regression with SPSS 26. Results show that lifestyle and brand image significantly influence purchase decisions, while free gifts do not have a partial effect. However, when tested simultaneously, the three variables showed a significant influence on purchase decisions, indicating that lifestyle, brand image and free gifts have a major impact on shaping consumer purchasing decisions